2008
DOI: 10.1089/jpm.2007.0149
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Variation in Timing of Hospice Referral: Does Having No Informal Caregiver Matter?

Abstract: Background-The length of hospice stay, as an indicator of timing of hospice referral, is an important outcome to examine in end-of-life care because it is relevant to the quality and cost efficiency of end-of-life care that patients receive. Although the majority receives nonmedical care from informal caregivers, many elderly hospice users rely on paid caregivers or staff of residential facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Five studies 47 51 describe how Hispanics are affected by caregiving and provide evidence of interventions to support them. A qualitative study using interviews of 30 Latino and white cancer-bereaved hospice family caregivers demonstrated poor hospice knowledge, familial decision making, denial and secrecy (did not approve that doctor informed patient that he/she was dying), and more satisfaction with hospice service among Latinos when compared to white caregivers.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies 47 51 describe how Hispanics are affected by caregiving and provide evidence of interventions to support them. A qualitative study using interviews of 30 Latino and white cancer-bereaved hospice family caregivers demonstrated poor hospice knowledge, familial decision making, denial and secrecy (did not approve that doctor informed patient that he/she was dying), and more satisfaction with hospice service among Latinos when compared to white caregivers.…”
Section: Resultsmentioning
confidence: 99%
“…16 Moreover, among patients with formal caregivers, minority patients had shorter length of stays in hospice prior to death or discharge compared to whites; however, there was no significant differences between patients with informal caregivers. 13 In contrast, another study showed that by 2000, the median survival for both blacks and whites was <30 days, and equal amounts (25%) of blacks and whites died within seven days of hospice admission. 17 The use of hospice services among blacks compared to whites was lower in the early 1990s, but these differences resolved by 2000.…”
Section: Introductionmentioning
confidence: 97%
“…Additional studies revealed that most physicians cite late hospice referrals as a direct result of family reluctance to accept patient prognosis and that death was near. 14,15 Research by Teno et al 16 revealed that hospice referrals were appropriate; however, short hospice stays affected the quality of end-of-life care received. Transition from personal culture to organizational culture depends on the individual physician’s medical training and acculturation into the health care system.…”
Section: Resultsmentioning
confidence: 99%